A change-prone zwitterionic hyperbranched terpolymer-based diabetic wound dressing. (June 2022) - Xie, Xianhua; Jin, Xin; He, Binbin; Zou, Yang; Yang, Jumin; Liu, Changjun; Kong, Xiaoling; Liu, Wenguang; Wang, Wei
Highlights: Hydrogel wound dressings demonstrate a strong anti-inflammatory capability by AP nanosheet. Hydrogel wound dressings are antibacterial as in situ reduced AgNPs by AP. Non-invasive dressing change can be facilitated by ion-strengthening and thermosensitive responses. Abstract: The long inflammation state and susceptibility to infection of a diabetic ulcer impairs wound healing. In this report, an in situ formed hydrogel dressing with antibacterial and anti-inflammatory activities is designed to nurse diabetic wounds. Firstly, a hyperbranched terpolymer (termed as HBPVD) is synthetized by a unique dynamically controllable reversible addition-fragmentation chain transfer (RAFT) polymerization of poly(ethylene glycol) diacrylate (PEGDA), 1-vinylimidazole (VI), and 2-(N-3-sulfopropyl-N, N-dimethyl ammonium) ethyl methacrylate (DMAPS). The resulted HBPVD is equipped with multi-acrylate end group that can be crosslinked with gelatin methacrylate (GelMA) to form a hydrogel in situ under UV light. The imidazole group in VI can chelate metal ions to enhance the mechanical strength of the hydrogels. The introduction of zwitterion DMAPS imparts the hydrogels thermosensitive and anti-fouling capability to get rid of the bacterial debris from wound beds. Meanwhile, the self-assembled ascorbyl palmitate (AP) nanosheet is encapsulated into the hydrogels, affording a strong anti-inflammatory capability and serving as a reservoir of reducing agent. Based on an Ag + -AP in situ -reduction method, Ag + complexed by VI in the hydrogel can be homogeneously reduced to Ag nanoparticles. The rheological results confirm that a solid HBPVD/GelMA hydrogel is obtained by UV light irradiation within 1 min. The strength of hydrogels is sharply increased by complexation of metal ions. A strong anti-bacterial ability against both gram-positive and gram-negative bacteria is achieved in HBPVD/GelMA/Ag/AP hydrogel. The HBPVD/GelMA/Ag/AP hydrogel dressing is administrated on humanized wound beds in diabetic rats, which can be conveniently changed by spraying 4 °C Cu 2+ solution that fleetly triggers both ion-strengthening and thermosensitive responses. The designed dressing presents a faster wound closure ratio with promoting epithelialization and the density of collagen, decreasing the expression level of pro-inflammatory factors (IL-1β, TNF-α), and improving the expression level of anti-inflammatory factor (IL-10). This change-prone hydrogel dressing with antibacterial and anti-inflammatory capability can provide a promising alternative method to repair diabetic wounds. Graphical abstract: Image, graphical abstract